Leituras dos objetos técnicos pelas lentes do campo CTS: o papel social da fotografia - Fernandes, Flávio Biazim (2022)
The purpose of this dissertation is to present an analysis of investigations focused on the STS field - Science, Technology and Society - based on discussions between fundamental authors such as Arlindo Machado, Lucia Santaella, Bruno Latour, Langdon Winner, Octavio Ianni, Susan Sontag, Walter Benjamin, Gilbert Simondon and Renato Ortiz. Based on Vilém Flusser's concepts, the research suggests a dialogue between them, permeating which particular ideas they have about the CTS concept associated with the characterizations of media art and photography, that is, a set of visual communications created by technical images. The verification starts from the assumption that it is necessary to understand these opinions and how they observe the interactions and communications between art, media and technical objects and, thus, question them to, in this way, develop our own point of view. Motivated to propose considerations about the impact of these overlaps between art and technology, the research presents questions about new artistic practices from the technological artifacts that integrate the so-called media art, taking as a reference photography as an important engine of transformation of modern western society from the end of the 19th century to the present day. For the development of the work, we based the methodology through a bibliographic review, seeking information in books, periodicals, magazines and articles. The STS field and its authors and authors from other fields such as sociology and semiotics were taken as support for the theoretical analysis.